كەرەنتينەو كاريگەرى لەسەر سروشتى په‌یوەندييە كۆمه‌ڵایه‌تییه‌كانی كۆمەڵگەى كوردى - صالح, میران محمد (Sulaimani Journal for Humanities, 2021)
The aim of the study is to clarify how the Coronavirus tragedy appeared, the concept of quarantine, the relationship between a citizen and a regional government, how to deal in light of these global, stable conditions, to know their impact on social relations and the level of health, economic and Self-awareness of community members, however, to know the opinions of the respondents regarding quarantine and how they deal with these conditions and their impact on the side Economic and health of the family and the self on the members of the Kurdish community. This study is one of the descriptive studies in which the social survey method was used in the sample. In the end, the study reached a number of results, including: 1-The study, 41% of the respondents, confirmed that the quarantine was not due to the raising of the level of problems and domestic violence. 2-The study showed, 73% of the respondents that they confirmed the quarantine was a reason for them to care more about prevention than treatment. 3-The study confirmed (65-75%) of the respondents that despite the harsh and catastrophic conditions of Corona virus, we have felt bad conditions among workers, street vendors, and the foreign poor in the region's camps. 4-The study showed (73%) of the respondents confirmed that these circumstances had pushed them not to purchase unnecessary goods and commodities. 5-The study showed (70.4%) of the respondents that the quarantine had proven to them the effective role of the police, traffic police, security men and the Peshmerga in an effective and necessary manner. 6-The study showed that the effect of quarantine had an effect on the family in general and on married couples in particular.